Detection and Surveillance of Invasive Aedes Mosquitoes in Spain: Implications for Arbovirus Risk and Public Health Preparedness - Marta Bononad Brugger; M. Adela Valero; Agustín Llopis-Gonzalez; Maria Morales-Suárez-Varela (Insects, 2026)
The expansion of invasive mosquito species of the genus Aedes has become a growing public health concern in Europe due to their role in the transmission of arboviruses such as dengue, Zika, and chikungunya. Early detection and surveillance of these vectors are essential to prevent the establishment of local transmission cycles. This study presents a review of surveillance reports and rapid risk assessments issued by the Health Alerts and Emergencies Coordination Centre of the Spanish Ministry of Health, complemented by relevant scientific literature on the presence and spread of Aedes albopictus, Aedes aegypti, and Aedes japonicus in Spain. The analysis describes the evolution of vector detection between 2004 and 2026, identifies geographical patterns of expansion, and examines the surveillance and response mechanisms implemented by Spanish health authorities. Particular attention is given to environmental, climatic, and socioeconomic factors that may facilitate the establishment of these invasive species. The results highlight the importance of strengthening entomological surveillance systems, improving coordination between national and regional health authorities, and enhancing early warning mechanisms to reduce the risk of arbovirus transmission in Spain. Unlike previous European reviews, this study integrates surveillance reports, grey literature, citizen science contributions, and scientific evidence to provide a comprehensive assessment of invasive Aedes surveillance in Spain and identify priority actions for strengthening arbovirus preparedness.